Immune Response on Optimal Timing and Fractionation Dose for Hypofractionated Radiotherapy in Non–Small-Cell Lung Cancer - Zhao, Xianlan; Li, Jixi; Zheng, Linpeng; Yang, Qiao; Chen, Xu; Chen, Xiewan; Yu, Yongxin; Li, Feng; Cui, Jianxiong; Sun, Jianguo (Frontiers in Molecular Biosciences, 2022)
Background: The intervention timing of immune checkpoint inhibitors (ICIs) and radiotherapy fractionations are critical factors in clinical efficacy. This study aims to explore dynamic changes of tumor immune microenvironment (TIME) after hypofractionated radiotherapy (HFRT) at different timepoints and fractionation doses in non-small cell lung cancer (NSCLC). Methods: In implanted mouse model, the experimental groups received HFRT 3.7Gy×4F, 4.6Gy×3F, 6.2Gy×2F, and 10Gy×1F respectively with a same biological equivalent dose (BED) of 20Gy. Tumor volume and survival time were compared with control group. Flow cytometry was performed to detect immune cells and their PD-1/PD-L1 expressions using tail-tip blood at different timepoints and tumor tissues at 48h after radiotherapy. In NSCLC patients, immune cells, PD-1/PD-L1 and cytokines were detected in peripheral blood for 4 consecutive days after different fractionation radiotherapy with a same BED of 40Gy. Results: Tumor volumes were significantly reduced in all experimental groups compared with control group, and the survival time in 6.2Gy×2F (P<0.05) was significantly prolonged. In tail-tip blood of mice, CD8+ T counts increased from 48h to 3 weeks in 4.6Gy×3F and 6.2Gy×2F, and CD8+ PD-1 shortly increased from 48h to 2 weeks in 6.2Gy×2F and 10Gy×1F (P<0.05). Dentritic cells (DC) were recruited from 2 weeks to 3 weeks (P<0.01). As for NSCLC patients, CD8+ T counts and PD-1 expression increased from 24h in 6.2Gy×4F, and CD8+ T counts increased at 96h in 10Gy×2F (P<0.05) in peripheral blood. DC cells were tentatively recruited at 48h and enhanced PD-L1 expression from 24h in both 6.2Gy×4F and 10Gy×2F (P<0.05). Besides, serum IL-10 increased from 24h in 6.2Gy×4F (P<0.05). Conversely, serum IL-4 decreased at 24h and 96h in 10Gy×2F (P<0.05). Conclusion: HFRT induces the increase of CD8+ T cells and positive immune cytokine response in specific period and fractionation doses. It was the optimal time window from 48h to 2 weeks for immune response, especially in 6.2Gy fractionation. While the best immune response was 96h later in 10Gy fractionation, delivering twice instead of single dose. During this time window, the intervention of immunotherapy may achieve a better effect.